Historical Drama for the Dissemination of Government Policies - et. al., Manissa Vasinarom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to study historical drama for the dissemination of government policies. The scope of the study focuses on the dissemination of the government policies of Thai leaders in the Rattanakosin period, using a mixed research method. The results showed that, historical drama was a communication tool for leaders to create their identity and present the image of the leaders and the country. There are 2 types of drama: comedy and tragedy. The drama content presented mainstream history and alternative history, including the way of life of the protagonist, the confrontation with crisis, and the outcome. The theme of the drama includes the personality of the leaders, the leader’s groups, the key situations, the ideals and practices of the leaders, and the contributions to the society. The role of historical drama in terms of policy dissemination is redundant and difficult to distinguish clearly. The prominent role of drama found in this study is for communication, education, entertainment, symbol of honor for royalties, public relations, image building, community identity, motivation, and treatment. The historical drama changed according to leadership, social, government, and government policies. The drama creation is based on historical data with modification according to the purposes of the creator and tastes of the audiences. Timely publishing will affect the popularity of the performance, and may lead to the changes that the leaders expect.